2004
DOI: 10.1093/jn/134.4.817
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Conjugated Linoleic Acid Positively Affects Immunologic Variables in Lactating Sows and Piglets

Abstract: We studied the effects of conjugated linoleic acid (CLA) on metabolic and immunologic variables in lactating sows and piglets. Gestating sows (n = 16) were assigned to 1 of 2 weight- and parity-matched groups supplemented with 0% (C) or 0.5% (T) of a CLA preparation containing 50% CLA isomers. Supplementation started in late pregnancy and continued throughout lactation. At weaning, 80 piglets, half from each group of sows, were assigned to 0% CLA (C) or 0.5% CLA (T). Thus, there were four groups of 20 piglets:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

20
59
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 46 publications
20
59
3
Order By: Relevance
“…In our experiment, pigs fed betaine and (or) CLA had reduced serum growth hormone, with no change in IGF-1 levels, which agree with the findings of Bontempo et al (2004) in lactating sows fed CLA. By contrast, Li et al (1999) found that CLA increases serum IGF-1 in rats, suggesting the hypothesis that CLA modulates body mass through mechanisms involving the IGF system.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our experiment, pigs fed betaine and (or) CLA had reduced serum growth hormone, with no change in IGF-1 levels, which agree with the findings of Bontempo et al (2004) in lactating sows fed CLA. By contrast, Li et al (1999) found that CLA increases serum IGF-1 in rats, suggesting the hypothesis that CLA modulates body mass through mechanisms involving the IGF system.…”
Section: Discussionsupporting
confidence: 91%
“…Work with 3T3-L1 adipose cells supported the evidence that CLA enhanced lipolysis (Park et al, 1997). However, contrary to Ostrowska et al (2002), we have found no serum NEFA change in pigs fed CLA diets and similar results were found in lactating sows (Bontempo et al, 2004). In this study, betaine had no effect in serum NEFA and similar results have previously been reported (Matthews et al, 1998;Øverland et al, 1999).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Rooke and Bland (2004) found that sow's diets supplemented with FO could increase IgG content in colostrum (P < 0.05). Bontempo et al (2004) and Rossi et al (2004) found that the addition of conjugated linoleic acid (CLA) increased IgG levels in colostrum (P < 0.05). However, the reports regarding the effects of l-carnitine and FO on IgG and IgA levels are not consistent.…”
Section: Discussionmentioning
confidence: 99%